Local delivery of growth factors using coated suture material - Fuchs, Thomas; Schmidmaier, Gerhard (The ScientificWorld journal, 2012)
The optimization of healing processes in a wide range of tissues represents a central point for surgical research. One approach is to stimulate healing processes with growth factors. These substances have a short half-life and therefore it seems useful to administer these substances locally rather than systemically. One possible method of local delivery is to incorporate growth factors into a bioabsorbable poly (D, L-lactide) suspension (PDLLA) and coat suture material. The aim of the present study was to establish a procedure for the local delivery of growth factors using coated suture material. Sutures coated with growth factors were tested in an animal model. Anastomoses of the colon were created in a rat model using monofilament sutures. These were either untreated or coated with PDLLA coating alone or coated with PDLLA incorporating insulin—like growth factor-I (IGF-I). The anastomoses were subjected to biomechanical, histological, and immunohistochemical examination. After 3 days the treated groups showed a significantly greater capacity to withstand biomechanical stress than the control groups. This finding was supported by the results of the histomorphometric. The results of the study indicate that it is possible to deliver bioactive growth factors locally using PDLLA coated suture material. Healing processes can thus be stimulated locally without subjecting the whole organism to potentially damaging high systemic doses.